Measurement of clinical decision-making by the Nurs.Comps, the twelve point postpartal check microcomputer simulation. - Sylvia BM (Measurement of Clinical Decision-making by the Nurs.comps, the Twelve Point Postpartal Check Microcomputer Simulation, 1989)
The purposes of this methodological study were: (a) to test one computer simulation instrument which measures the phenomena of clinical decision making for a specific content area; (b) to determine if clinician related variables of age and education influence clinical decision making outcomes; and (c) to examine the utility and practicality of a computer simulation program as a measure of clinical decision making outcomes. To determine test-retest reliability 19 graduating students from each of three types of undergraduate nursing education programs completed the computer simulation program on two separate occasions. The Pearson r between the scores for Time I and Time II was 0.80 for the intervention scores with the remaining scores less than 0.60. The percent of agreement exceeded 0.84 for the five pairs of scores. To determine content validity nine nursing experts completed the computer simulation program and two rating scales for item to nursing process congruence and relevance. Proficiency scores for each panel member exceeded 90 percent. Evidence to support content validity at the item level was inconsistent with few items achieving the Congruency Index cut-off score of 0.70. Percent agreement for relevance of items to the assessment, planning, intervention, and evaluation components were 0.80, 0.75, and 0.33, and 1.00. Construct validity was determined using the contrasted groups and hypothesis testing approach. Data analysis consisting of the t test revealed significant differences between the mean scores of the contrasted groups of 20 beginning nursing students and 21 expert staff nurses. One-Way Analysis of Variance was used to determine hypothesized differences in clinical decision making outcomes of 74 graduating students from the three nursing education program types. Significant differences (F (2,71) = 6.9968, p =.0017) in group means scores were determined for the intervention nursing process component. The Scheffe multiple comparison procedure determined the significant difference was between the associate degree and generic baccalaureate group means. Results of the t-test revealed significant differences in the mean scores of experienced and inexperienced graduating students for three of the scores. Evaluations of the utility and practicality of the program were positive.